Perempuan dan Pertumbuhan Gereja dalam Komunitas Kristen mula-mula: Fokus pada Lukas 8:1-3 - Masambe, Helen Gratia; Palempung, Rivay Bobby; Lumintang, Ferry Sonny Nixon (Educatio Christi, 2025)
In the context of Minahasa, in fact women have been given equal opportunities with men. But it is also undeniable fact that women in Minahasa are also face a lot of struggles. Some women become objects to domestic or workplace violence, trafficking, divorce, marginalization in the workplace, etc. There are women who are forced or willing to leave their jobs because of the demands of marriage and family life. So, the problem is, even though the society or even the church provides space for women to play an active role, some women reject it with cultural or social reasons. The problem lies with women who cannot use the opportunities to explore their abilities that God has given them to work with others in God’s missionary work. This research aims to analyze the role of the women who followed Jesus in church growth according to Luke 8:1-3. This research uses qualitative research methods by collecting data from books and journals that will be analyzed to get the conclusion. The result of this research reveals that women can play active roles in the society and church ministry using all their capacities that God has given to them. A change of thought is necessary if what is expected is a change of action. Change of thinking from women themselves to be willing to fight for liberation and transformation in her life and other people’s life through church’s and society’ mission/ministry. Keywords: Luke, woman, Jesus’s follower, church, ministry.